Transcriptome analysis and gene expression analysis related to salinity-alkalinity and low temperature adaptation of Triplophysa yarkandensis - Zhang, Xuejing; Wang, Tai; Zhai, Dongdong; Liu, Hongyan; Xiong, Fei; Wang, Ying (Frontiers in Genetics, 2023)
T. yarkandensis is a common species of Triplophysa, and it is distributed in Shule river of Hexi Corridor, of Gansu province in China. In order to enrich gene database resources and explore the environment adaptation of T. yarkandensis, fifteen tissues were collected from three adult T. yarkandensis for transcriptome sequencing and de novo assembly. Nine major international gene annotation databases (NR, COG, egg_NOG, TrEMBL, Pfam, KOG, Swiss prot, KEGG and Gene Ontology) were utilized to annotate unigenes. A detailed study was conducted to explore the gene expression and the differentially expressed genes among five tissues (brain, heart, kidney, liver and spleen). In addition, the current study showed that candidate genes involved in salinity-alkalinity and low temperature adaptation were differentially expressed in tissues of T. yarkandensis. Precisely, mapk1, abcc1, gpx1, gpx4, cat and aqp1 genes participated in the regulation process of salinity-alkalinity adaptation, and elovl4, acaca, fasn, acaa2, acox1 and acox3 genes were involved in fatty acid metabolism and closely associated with low temperature adaptation. On the one hand, it was found that the expression of these genes varied among different tissues, and the important pathways involved in these genes were mapped. Furthermore, we analyzed mapk1 and acox1 genes in depth to obtain the predicted gene structure and important amino acid sites. The transcriptome information in this study will be conducive to provide further understanding for the molecular level research and exploration of the environmental adaptation of T. yarkandensis.